Molecular hydrogen protects human lymphocyte AHH-1 cells against 12C6+ heavy ion radiation. (December 2013) - Yang, Yanyong; Gao, Fu; Zhang, Hong; Hunag, Yijuan; Zhang, Pei; Liu, Cong; Li, Bailong; Cai, Jianming
Abstract Purpose: To investigate the potential protective role of molecular hydrogen (H2) against 12C6+ heavy ion radiation, which is a major hazard for space travel and has been also widely used in heavy ion radiotherapy. Materials and methods: H2 was dissolved in Roswell Park Memorial Institute (RPMI) 1640 medium under high pressure (0.4 Mpa) to a saturated level by using an apparatus produced by our department. A 2-[6-(4′-hydroxy) phenoxy-3H-xanthen-3-on-9-yl] benzoate (HPF) probe and a 2′, 7′-Dichlorodihydrofluorescein diacetate (H2DCFH-DA) fluorescent dye were used to measure the intracellular reactive oxygen species (ROS) level. Cell apoptosis were determined by double-staining with Annexin V-fluorescein isothiocyanate (Annexin V-FITC) and propidium iodide (PI) as well as a Hoechst 33342 staining method alternatively. Subsequently, cell cycle analysis was performed using a PI staining method and the expression of apoptotic protein was examined by Western blot. Results: In this study, we demonstrated H2 reduced ROS level in Human lymphocyte AHH-1 cells as well as in the radiolysis of water. Our data also showed H2 attenuated 12C6+ radiation- induced cell apoptosis and also alleviated radiation-induced G2/M cell cycle arrest. Heavy ion radiation-induced Caspase 3 activation was also inhibited by H2 treatment. Conclusion: In conclusion, these data showed that H2 attenuated 12C6+ radiation-induced cell apoptosis through reducing the ROS level and modulating apoptotic molecules, thus indicating the potential of H2 as a safe and effective radioprotectant.